The international arbitration rulebook a guide to arbitral regimes - Ali, Arif Hyder (Kluwer Law International B.V., 2019)
With this eminently practical book, contract negotiators, counsel and arbitrators can confidently navigate any international arbitration. Thorough coverage of the applicable rules and guidelines enables parties and/or the tribunal to design bespoke arbitration procedures based upon the various rules of leading regimes. Arbitral institutions can survey the different approaches and identify emerging best practices in the designing and drafting of arbitral regimes. Designed to cover the broad range of issues that are addressed in arbitration rules in a straightforward, practical style, this book will be a valuable resource for practitioners and students alike, both those who are new to arbitration and those with considerable knowledge and experience.